Analysis of Micro and Small Business Owners' Perceptions of The Benefits of Sharia Insurance In Managing Business Risks - Adinda Rizki Fadilah; Muhammad Arif; Atika Atika (STAI Serdang Lubuk Pakam, 2023)
This study aims to analyze the perceptions of Micro and Small Enterprise (MSE) owners towards the benefits of sharia insurance in managing business risks. This research is located in Serdang Bedagai, using a case study-based qualitative research method. Data was obtained through interviews with 10 owner research informants, who were selected based on the coverage of various business sectors and income levels. The results revealed that MSE owners have a positive perception of the benefits of Islamic insurance in managing business risks. Although the understanding of Islamic insurance is limited, MSE owners who have not adopted Islamic insurance have varied perspectives according to their understanding and needs. The majority expressed readiness to use sharia insurance if the premium is affordable and the benefits are as needed. However, there are also those who still need further education regarding the concept and halalness of Islamic insurance products. This positive perception shows the potential for growth and adoption of sharia insurance in Serdang Bedagai Regency. However, there are also challenges, namely that there are still owners who do not fully understand the basic principles of sharia insurance.